1995
DOI: 10.1136/gut.37.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Reversible effect of phytohaemagglutinin on the growth and metabolism of rat gastrointestinal tract.

Abstract: The lectin, phytohaemagglutinin, present in beans survives passage through the gastrointestinal tract in a biologically and immunologically intact form. It is known that by binding to the brush border membranes of the small intestine phytohaemagglutinin induces its hyperplastic growth. However, its effect on the other parts of the gut are not known. This study considered the dose and time dependent changes in the gastrointestinal tract exposed to phytohaemagglutinin. Lectin binding was detected by polyclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 16 publications
4
66
0
3
Order By: Relevance
“…Similar changes were evident in rats fed lectin (520 mg/kg body weight per d) from Phaseolus vulgaris var. processor (Oliveira et al 1988;Bardocz et al 1995) and were likely to have been due to crypt cell hyperplasia, increased epithelial cell size, thickening of the smooth muscle layer and increased production of mucus (Pusztai, 1991;Bardocz et al 1995). Rates of epithelial cell turnover would also have been greatly increased (Pusztai, 1991;Bardocz et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar changes were evident in rats fed lectin (520 mg/kg body weight per d) from Phaseolus vulgaris var. processor (Oliveira et al 1988;Bardocz et al 1995) and were likely to have been due to crypt cell hyperplasia, increased epithelial cell size, thickening of the smooth muscle layer and increased production of mucus (Pusztai, 1991;Bardocz et al 1995). Rates of epithelial cell turnover would also have been greatly increased (Pusztai, 1991;Bardocz et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the normal healthy gut accounts for 20-35 % of whole-body protein turnover despite forming only 3 -6 % of body weight (Reeds et al 1999). However, turnover times can be reduced to 16-24 h and cell proliferation rates increased when the intestine is stimulated to grow by lectin (King et al 1986;Pusztai, 1991;Bardocz et al 1995Bardocz et al , 1996. The already high requirements of the gut for nutrients are therefore greatly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, plant lectins have been classified according to the mono-or oligosaccharide that prevents the lectin from agglutinating eryth precipitating glycoconjugates in vitro (from Van Damme et al, 1998) ed as "one of the most important physiologically active ing i nals in the diet" . his is due to their widespread occurrence in plants and crops, their partial resistance to heat denatur Plant lectins have been describ red ents and potent exogenous biological sig T ation as well as to breakdown during passage through the digestive tract (Hara et al, 1984;Pusztai et al, 1990;Bardocz et al, 1995), and their interaction with endogenous surface receptors of the intestinal epithelial cells of all higher and lower animals that ingest them. (Roth, 1987;.…”
Section: Biological Effects In Fish General Considerationsmentioning
confidence: 99%
“…The role of lectins in bacterial enteric conditions was first demonstrated by Banwell et al (1988), whose results were later confirmed and extended by Pusztai et al (1993), Bardocz et al (1995) and Pusztai et al (1997). In their view, intestinal bacterial counts are higher in lectin-fed animals, but lectins also may exert beneficial influence by enhancing epithelial layer replacement.…”
Section: Soybean Lectinsmentioning
confidence: 87%
“…Soybean lectin binds to the intestinal epithelium and can be reisolated from the faeces. In rats raw kidney bean lectin binds to epithelial cells in the stomach, the brush border Acta Veterinaria Hungarica 52, 2004 membrane in the small intestine, and epithelial cells of the caecum and colon (King et al, 1986;Bardocz et al, 1995). Kidney bean lectin caused shortening of small intestinal villi and epithelial damage (King et al, 1980).…”
Section: Soybean Lectinsmentioning
confidence: 99%